2018
DOI: 10.1029/2018gb005980
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistent Response of Arctic Permafrost Peatland Carbon Accumulation to Warm Climate Phases

Abstract: Northern peatlands have accumulated large carbon (C) stocks since the last deglaciation and during past millennia they have acted as important atmospheric C sinks. However, it is still poorly understood how northern peatlands in general and Arctic permafrost peatlands in particular will respond to future climate change. In this study, we present C accumulation reconstructions derived from 14 peat cores from four permafrost peatlands in northeast European Russia and Finnish Lapland. The main focus is on warm cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 81 publications
1
22
2
Order By: Relevance
“…However, due to the complexity of interactions between these factors and the highly heterogeneous nature of peatlands, links between peat carbon accumulation and any individual environmental variables are not straightforward (e.g. Loisel & Garneau, ; Piilo et al, ; Zhang, Gallego‐Sala, et al, ). We did not observe any changes in plant functional types, for example, from Sphagnum to shrubs (Tuittila et al, ); thus, we assume that the detected variation in CAR is largely due to variations in moisture and temperature, although changes within one plant functional type, for example, moss community, might alone could still drive changes in carbon accumulation due to different photosynthesis and decomposition rates at the species level (Hajek, Tuittila, Ilomets, & Laiho, ; Kangas et al, ; Laine, Juurola, Hajek, & Tuittila, ; Turetsky, Crow, Evans, Vitt, & Wieder, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the complexity of interactions between these factors and the highly heterogeneous nature of peatlands, links between peat carbon accumulation and any individual environmental variables are not straightforward (e.g. Loisel & Garneau, ; Piilo et al, ; Zhang, Gallego‐Sala, et al, ). We did not observe any changes in plant functional types, for example, from Sphagnum to shrubs (Tuittila et al, ); thus, we assume that the detected variation in CAR is largely due to variations in moisture and temperature, although changes within one plant functional type, for example, moss community, might alone could still drive changes in carbon accumulation due to different photosynthesis and decomposition rates at the species level (Hajek, Tuittila, Ilomets, & Laiho, ; Kangas et al, ; Laine, Juurola, Hajek, & Tuittila, ; Turetsky, Crow, Evans, Vitt, & Wieder, ).…”
Section: Discussionmentioning
confidence: 99%
“…Apparent CAR (ACAR; g C m −2 year −1 ) was calculated by multiplying the bulk density of a depth‐specific increment by its C content and by the accumulation rate. Peat decay modelling (Clymo, ) was used to derive the allogenic impact‐forced carbon accumulation variations (Zhang, Gallego‐Sala, et al, ). The Clymo model (1984) was first applied on the cumulative peat mass (bulk density) data to derive peat addition rate ( p ) and peat decay coefficient ( α ) using the curve fitting method.…”
Section: Methodsmentioning
confidence: 99%
“…Our results indicated high accumulation rates during recent decades. Previous studies focussing on both the last millennium (Charman et al 2013, Garneau et al 2014, Loisel et al 2014 and recent decades (Zhang et al 2018b) showed that relatively high accumulation rates are likely caused by increased carbon inputs rather than by reduced decomposition. We acknowledge the difficulty of interpreting the recent peat accumulation rates due to the incomplete decomposition process and lower compaction of the surface peat and restraints on the chronologies.…”
Section: Drivers Behind Accumulation Patternsmentioning
confidence: 98%
“…However, longer, warmer growing seasons and changes in Arctic precipitation regimes (Bintanja & Selten, ; Kattsov et al, ; Kopec et al, ) may stimulate carbon capture through enhanced plant productivity in peatlands and the transition of minerotrophic wetlands into organic peatlands (Charman et al, , ; Gallego‐Sala et al, ; Morris et al, ). Recent evidence shows an inconsistent response of Arctic and sub‐Arctic peatlands to warming in terms of carbon accumulation (Zhang, Gallego‐Sala, et al, ).…”
Section: Introductionmentioning
confidence: 99%